Respuesta :

Simplify the expression....
you have...
[tex]( x^{ \frac{4}{3} } )( x^{ \frac{2}{3} } )[/tex]
simplifying it...
[tex] x^{2} [/tex]
The product of the two factors....
Thus, your answer. 

Answer:  The required product is [tex]x^2.[/tex]

Step-by-step explanation:  We are given to find the product of the following two factors.

[tex]P=(x^\frac{4}{3})(x^\frac{2}{3}).[/tex]

We will be using the following property of exponents:

[tex]a^x\times a^y=a^{x+y}.[/tex]

We have

[tex]P\\\\=(x^\frac{4}{3})(x^\frac{2}{3})\\\\=x^\frac{4+2}{3}\\\\=x^\frac{6}{3}\\\\=x^2.[/tex]

Thus, the required product is [tex]x^2.[/tex]